2015
DOI: 10.1371/journal.pone.0128513
|View full text |Cite
|
Sign up to set email alerts
|

The Forkhead Transcription Factor FOXP2 Is Required for Regulation of p21WAF1/CIP1 in 143B Osteosarcoma Cell Growth Arrest

Abstract: Mutations of the forkhead transcription factor FOXP2 gene have been implicated in inherited speech-and-language disorders, and specific Foxp2 expression patterns in neuronal populations and neuronal phenotypes arising from Foxp2 disruption have been described. However, molecular functions of FOXP2 are not completely understood. Here we report a requirement for FOXP2 in growth arrest of the osteosarcoma cell line 143B. We observed endogenous expression of this transcription factor both transiently in normally d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 48 publications
1
24
0
Order By: Relevance
“…However, higher levels of expressions of GRIAL1, SGOL1 and Igfbp6 were found within parietal bone that displayed anti-proliferative feature, such as overexpression of GRIAL1 is anti-proliferative [28], and SGOL1 and Igfbp6 are involved in cell apoptosis [29-31]. Foxp2 can increase cell differentiation without affecting cell proliferation and cell survival [32], and transient upregulation of Foxp2 in pre-osteoblast mesenchymal cells regulates a p21-dependent growth arrest checkpoint [33]. Our findings are consistent with the publication that osteoblasts from the neural crest-derived frontal bone are less differentiated, grow faster compared to parietal bone-derived osteoblasts [3].…”
Section: Discussionmentioning
confidence: 99%
“…However, higher levels of expressions of GRIAL1, SGOL1 and Igfbp6 were found within parietal bone that displayed anti-proliferative feature, such as overexpression of GRIAL1 is anti-proliferative [28], and SGOL1 and Igfbp6 are involved in cell apoptosis [29-31]. Foxp2 can increase cell differentiation without affecting cell proliferation and cell survival [32], and transient upregulation of Foxp2 in pre-osteoblast mesenchymal cells regulates a p21-dependent growth arrest checkpoint [33]. Our findings are consistent with the publication that osteoblasts from the neural crest-derived frontal bone are less differentiated, grow faster compared to parietal bone-derived osteoblasts [3].…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence has indicated that the expression of FOX genes, including FOXC2 27 , FOXF1 28 , FOXL1 29 , FOXM1 30 , 31 , FOXO1 32 , 33 and FOXP2 34 , is disrupted in osteosarcoma cells and primary tumor biopsy samples. As shown in Table 1 , according to their expression in osteosarcoma cells and primary tumor biopsy samples, these FOX genes can be divided into two groups: oncogenes and anti-oncogenes.…”
Section: Expression Of Fox Genes In Osteosarcomamentioning
confidence: 99%
“…Oncogenes primarily include FOXC2 , FOXM1 and FOXP2 , and the elevated expression level of these genes has been observed in osteosarcoma cells, which is positively correlated with tumor size, clinical stage, pathological facture, and distant metastasis 27 - 29 . Anti-oncogenes primarily include FOXF1 , FOXL1 and FOXO1 , and decreased or absent expression levels of these genes were examined in osteosarcoma cells and primary tumor biopsy samples 30 - 34 .…”
Section: Expression Of Fox Genes In Osteosarcomamentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, high expression of FOXP2 has been associated with a bad prognosis in prostate cancer [10], neuroblastoma [11] and multiple mieloma [12]. On the other hand, other studies have reported an association between FOXP2 expression and a better prognosis in breast cancer [13], liver cell carcinoma [14], osteosarcoma [15] and gastric cancer [16]. Thus, whether FOXP2 is a tumor suppressor or tumor-promoting gene is matter of controversy.…”
Section: Introductionmentioning
confidence: 99%